Rapid necrosis: a novel plant resistance mechanism to 2, 4-D. Issue 1 (September 2019) - Queiroz, Andrew R. S. de; Delatorre, Carla A.; Lucio, Felipe R.; Rossi, Caio V. S.; Zobiole, Luiz H. S.; Merotto, Aldo
Abstract: Plants of Sumatran fleabane [ Conyza sumatrensis (Retz.) E. Walker] were identified in a field with an unusual rapid leaf-injury herbicide symptoms after application of 2, 4-D in mixture with glyphosate. The objectives of this study were to confirm the occurrence of resistance to 2, 4-D herbicide and to characterize the occurrence of rapid necrosis as the mechanism associated with the herbicide resistance in C. sumatrensis . The studies performed were an initial screening, effect of 2, 4-D alone and associated with glyphosate, cross- and multiple-resistance evaluation, effect of commercial formulation and analytical product, and rate of H2 O2 evolution. The Marpr9-rn accession was identified with rapid necrosis symptoms and survival to 804 g ae ha −1 of 2, 4-D. The resistance factor to the herbicide 2, 4-D was 18.6 at 49 d after spraying. The analytical product 2, 4-D and the commercial formulation resulted in similar symptoms of rapid necrosis. This symptom did not occur for the six other auxinic herbicides (dicamba, florpyrauxifen-benzyl, fluroxypyr, halauxifen-methyl, picloram, and triclopyr), indicating absence of cross-resistance. Multiple resistance to the herbicides paraquat, saflufenacil, and ammonium glufosinate was not identified in the Marpr9-rn population. However, survival following treatment with the herbicides glyphosate and chlorimuron-ethyl occurred. The evolution of H2 O2 began at 15 min after application and was less pronounced in low light. These results indicate the first case of resistance to 2, 4-D and occurrence of rapid necrosis in C. sumatrensis .